THU0142 High Similarity between ex-vivo Inhibited Cytokine Profiling by Golimumab and Adalimumab as A Putative Explanation for Inferior Treatment Response To Golimumab after Adalimumab Failure in Rheumatoid Arthritis. (15th July 2016) - Tweehuysen, L.; Schraa, K.; Netea, M.; van den Hoogen, F.; Joosten, L.; den Broeder, A.
Abstract : Background: Better prediction of treatment response to biologics in rheumatoid arthritis (RA) would contribute to optimal individualised treatment. Clinical data suggest that the response of RA patients to treatment with golimumab is much lower among those who switched from adalimumab compared with those who had previously received etanercept or infliximab. 1 In order to elucidate the mechanism behind this difference in response to sequential biologic treatment, we have performed ex-vivo inhibited cytokine profiling. Objectives: To compare the ex-vivo effect of six different biologics on multi-cytokine profiles of RA patients. Methods: In a prospective longitudinal prediction cohort study (BIO-TOP [Biologic Individual Optimised Treatment Outcome Prediction]), blood samples were obtained from patients at baseline (before start biologic). Within 24 hours peripheral blood mononuclear cells (PBMCs) were isolated, washed and pre-incubated for one hour with the therapeutic concentration of six different biologics (adalimumab and golimumab (anti-TNF-α), etanercept (TNFR-Fc) abatacept (CTLA4-Ig), rituximab (anti-CD20) and tocilizumab (anti-IL-6R)). Subsequently, the cells were stimulated with Candida albicans or Pam3Cys. Supernatants were harvested after 24 hours and stored at -20C. The cytokine concentrations of IL-1β, IL-6 and TNF-α were determined by ELISA. The correlation of absolute changes of cytokine levels after inhibition by each biologic were calculated and analysed by means of Spearman rank correlations (rs ). Results: Ex-vivo cytokine profiling was performed in 71 patients. The absolute change of cytokine level after inhibition by golimumab was significantly (p<0.001) correlated with the absolute change of cytokine level after inhibition by adalimumab for both IL-1β, IL-6 and TNF-α (Figure ). In other words, the cytokine profile after inhibition by golimumab or adalimumab was moderately to highly correlated with each other, while the correlation with the cytokine profile after inhibition by etanercept was much lower for both. Correlations between the cytokine profiles after inhibition by any of the three TNF inhibitors and cytokine profiles after inhibition by any non-TNFi were all weak (data not shown; all rs <0.6). Conclusions: The high similarity between ex-vivo inhibited cytokine profiling by golimumab and adalimumab provides a putative explanation for the previously found inferior treatment response to golimumab after adalimumab failure in RA. This interesting finding is relevant for clinical practice, because it seems that RA patients who are non-responsive to adalimumab should not switch to golimumab and vice-versa. Furthermore, the similarity in both cytokine profile and clinical outcome for golimumab and adalimumab suggests that ex-vivo inhibited cytokine profiling could be a predictor of individual treatment response to biologics. This is currently being investigated in the BIO-TOP study. References: Smolen JS et al. Insights into the efficacy of golimumab plus methotrexate in patients with active rheumatoid arthritis who discontinued prior anti-tumour necrosis factor therapy: post-hoc analyses from the GO-AFTER study. Ann Rheum Dis 2014;73:1811–1818 Disclosure of Interest: None declared